2019
DOI: 10.1108/hff-08-2018-0465
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of forced convection in a bi-disperse porous medium channel by creating new porous micro-channels inside the porous macro-blocks

Abstract: Purpose Porous medium has always been introduced as an environment for increasing heat transfer in cooling systems. However, increase in heat transfer and resolving pressure drop in the fluid flow have been focused on by researchers.The purpose of this paper is to study the effects of creating porous micro-channels inside porous macro-blocks to optimize system performance in channels. Design/methodology/approach To simulate flow field, a developed numerical code that solves Navier–Stokes equations by finite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…In this step, the external magnetic force (F=qvB sin(wt)) inserted on fluid atoms in non-ideal nanochannel and equilibrated atomic system for 1 ns. After this time energy calculation of all atoms show that, this time is sufficient for equilibration of system (Qi et al , 2019; Zhao et al , 2019a; Mei et al , 2019; Wang et al , 2019; Safaei et al , 2019; Vo et al , 2019; Zhai et al , 2019; Zhao et al , 2019b; Sarafraz et al , 2019c; Tlili et al , 2018a; Aman et al , 2018; Tlili et al , 2018b; Khan and Tlili, 2018; Sarafraz et al , 2019a, 2019b; Tlili et al , 2019; Shadloo, 2019; Hopp-Hirschler et al , 2019; Sadeghi et al , 2018; Hopp-Hirschler et al , 2018; Shadloo and Hadjadj, 2017; Sharma et al , 2019; Méndez et al , 2018; Piquet et al , 2019; Nguyen et al , 2019; Shenoy et al , 2019; Karimipour et al , 2014; Karimipour et al , 2015; Goodarzi et al , 2018; Ranjbarzadeh et al , 2017a, 2017b; Karimipour et al , 2018a; Afrand et al , 2016; Alrashed et al , 2018; Esfe et al , 2014; Karimipour et al , 2018b; Arabpour et al , 2018; Safaei et al , 2018; Karimipour et al , 2016; Jalali and Karimipour, 2019; Goodarzi et al , 2019; Tian et al , 2019; Gholamalizadeh et al , 2019; Mozaffari et al , 2019; Salimpour et al , 2019; Nazarafkan et al , 2019; Rajabzadeh et al , 2019; D’Orazio and Karimipour, 2019; Sulgani and Karimipour, 2019; Nafchi et al , 2019; Ershadi and Karimipour, 2018; Nojoomizadeh et al , 2018). Figures 3 and 4 show potential energy of system.…”
Section: Resultsmentioning
confidence: 99%
“…In this step, the external magnetic force (F=qvB sin(wt)) inserted on fluid atoms in non-ideal nanochannel and equilibrated atomic system for 1 ns. After this time energy calculation of all atoms show that, this time is sufficient for equilibration of system (Qi et al , 2019; Zhao et al , 2019a; Mei et al , 2019; Wang et al , 2019; Safaei et al , 2019; Vo et al , 2019; Zhai et al , 2019; Zhao et al , 2019b; Sarafraz et al , 2019c; Tlili et al , 2018a; Aman et al , 2018; Tlili et al , 2018b; Khan and Tlili, 2018; Sarafraz et al , 2019a, 2019b; Tlili et al , 2019; Shadloo, 2019; Hopp-Hirschler et al , 2019; Sadeghi et al , 2018; Hopp-Hirschler et al , 2018; Shadloo and Hadjadj, 2017; Sharma et al , 2019; Méndez et al , 2018; Piquet et al , 2019; Nguyen et al , 2019; Shenoy et al , 2019; Karimipour et al , 2014; Karimipour et al , 2015; Goodarzi et al , 2018; Ranjbarzadeh et al , 2017a, 2017b; Karimipour et al , 2018a; Afrand et al , 2016; Alrashed et al , 2018; Esfe et al , 2014; Karimipour et al , 2018b; Arabpour et al , 2018; Safaei et al , 2018; Karimipour et al , 2016; Jalali and Karimipour, 2019; Goodarzi et al , 2019; Tian et al , 2019; Gholamalizadeh et al , 2019; Mozaffari et al , 2019; Salimpour et al , 2019; Nazarafkan et al , 2019; Rajabzadeh et al , 2019; D’Orazio and Karimipour, 2019; Sulgani and Karimipour, 2019; Nafchi et al , 2019; Ershadi and Karimipour, 2018; Nojoomizadeh et al , 2018). Figures 3 and 4 show potential energy of system.…”
Section: Resultsmentioning
confidence: 99%
“…The SiO 2 and the CNT-SiO 2 deviations decreased almost 0.00705 and 0.004425%, respectively, individually. It is well-known that heat transfer enhanced after: increasing in the “Vol.%” (Das et al , 2003); “T” increment (Sarkar and Selvam, 2007); adding CNT (Jha and Ramaprabhu, 2009), to the Silica/Water mono nanofluid; however, the present work method had not been used before (Salimpour et al , 2020; Peng et al , 2019; Wu et al , 2019; Rajabzadeh et al , 2019; He et al , 2019; Bagherzadeh et al , 2019).…”
Section: Resultsmentioning
confidence: 92%
“…It is observed that thickness plays significant role than the width of porous partition. Rajabzadeh and Hojaji(2019) have created porous micro-channels inside macro-blocks to enhance heat transfer performance. The result shows a positive result with a significant decrease in pressure drop.…”
Section: Introductionmentioning
confidence: 99%